Implications of RNA Viruses in the Male Reproductive Tract: An Outlook on SARS-CoV-2 - Zafar, Mohammad Ishraq; Yu, Jiangyu; Li, Honggang (Frontiers in Microbiology, 2021)
Emerging viral infections continuously pose a threat to human wellbeing. Several RNA viruses have managed to establish access to the male reproductive tract and persist in human semen. Epidemiologically, it is important for the public to know whether a virus can be transmitted sexually, especially if it can be transmitted while the patient is an asymptomatic carrier, assumed to be fully recovered or during the infection’s incubation period. From the clinical perspective, negative impacts in the male reproductive tract associated with RNA virus infection have been described including orchitis, epididymitis, impaired spermatogenesis, a decrease in sperm quality, which can affect male fertility at different time intervals. The viral invasion into the testis may be due to the disrupted anatomical barriers of the testis by the inflammatory responses, and the persistence of the virus in the semen may be facilitated by the testicular immune privilege. In this review, the current knowledge about other RNA virus that affect the male reproductive health provides the framework to discuss the impact of SARS-CoV-2 pandemic. The molecular mechanisms, sexual transmission and viral impacts for patients of mumps, HIV, Zika and Ebola viruses are explored. We discuss the current knowledge about the impact of SARS-CoV-2 on the male reproductive tract regarding the viral presence in semen, its impact on sexual organs and sperm quality. To date no sexual transmission of SARS-CoV-2 has been reported, whereas the identification of viral particles in semen remains conflicting. In light of the preliminary analyses conducted, it is important to continue to investigate the long-term health effects of SARS-CoV-2 upon the reproductive tract.